1984
DOI: 10.1002/1097-4679(198407)40:4<901::aid-jclp2270400406>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health of young adults who experienced early parent death: MMPI trends

Abstract: Psychological effects that result from childhood parent loss by death are of substantial clinical and research importance. Parent loss has been linked with various psychopathology, though little is known of its effects on subsequent psychological health (a) as a function of the child's sex; (b) in normal individuals; (c) where early parent separation also has occurred. This study provides data on the Minnesota Multiphasic Personality Inventory‐168 (MMPI‐168) that address these issues. Ss were normals (16 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Therefore, it might be expected that the death of a parent would adversely affect the development of ROLE relationships. Several studies (e.g., Dietrich, 1984;Hepworth, Ryder, & Dreyer, 1984;Jacobson & Ryder, 1968;Murphy, 1986-87;Silverman, 1987), not based on a personal construct perspective, have studied the effects of death on interpersonal relationships for people who have lost a parent to death while they were adolescents. While some studies (e.g., Silverman, 1987) report that subjects see no connection between the death of their parent and their intimate relationships, other studies have shown such an effect.…”
mentioning
confidence: 99%
“…Therefore, it might be expected that the death of a parent would adversely affect the development of ROLE relationships. Several studies (e.g., Dietrich, 1984;Hepworth, Ryder, & Dreyer, 1984;Jacobson & Ryder, 1968;Murphy, 1986-87;Silverman, 1987), not based on a personal construct perspective, have studied the effects of death on interpersonal relationships for people who have lost a parent to death while they were adolescents. While some studies (e.g., Silverman, 1987) report that subjects see no connection between the death of their parent and their intimate relationships, other studies have shown such an effect.…”
mentioning
confidence: 99%
“…There is some consensus that loss of a parent in childhood is associated with a higher incidence of emotional and personality problems (Dietrich, 1984) and with higher rates of psychiatric consultations (Seligman, Gleser, Raun, & Harris, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The literature on bereavement has also identified several long-term negative consequences of early parental death for adult outcomes. Schizophrenia (Wahl, 1956), suicide (Crook & Raskin, 1975), alcoholism (Birtchnell, 1972), social introversion (Dietrich, 1984), and loss of seli-esteem (Dizmang, 1969) have all been reported by adults who experienced a parental death during childhood. Denes-Raj and Ehrlichman (1991) foimd that college students who had lost at least one parent during childhood predicted a shorter life span for themselves than students with both parents still Uvmg.…”
Section: Death and The Familvmentioning
confidence: 99%
“…This is fiuther complicated by the fact that there have been few attenq)ts to examine the long-term effects of early parent death among adults who do not exhibit overt psychiatric symptoms (Finkelstein, 1988). Dietrich (1984) has noted that "the amount of research that deals with nonpsychiatric, nonpatient populations is quite Umited and needs to be expanded" (p. 901).…”
Section: Death and The Familvmentioning
confidence: 99%
See 1 more Smart Citation